Microcephaly and Zika virus infection in Brazil - Trindade, Cleide Enoir Petean [UNESP]; de Souza Rugolo, Lígia Maria Suppo [UNESP] (American Academy of Pediatrics (AAP), 2016)
The Zika virus was discovered incidentally in Uganda in 1947 and had remained confined to an equatorial zone across Africa and Asia. A great outbreak of Zika virus was described in Micronesia (2007) and in Polynesia (2013–2014). An epidemic Zika virus infection was reported in 2015 in South and Central America and in the Caribbean. In Brazil, the first autochthonus case was reported in May 2015 in the northeastern region of the country and spread quickly to 22 states. Epidemiologic evidence suggests that this outbreak is associated with the increased number of infants born with congenital microcephaly in 2015–2016. Since April 2016, 6, 906 cases suspected of microcephaly have been reported to the government. Of these, 4, 046 (58.6%) were still in investigation; 1, 814 cases were excluded; and 1, 046 were confirmed using brain image diagnosis. Initial research on isolating and sequencing the Zika virus in brains and amniotic liquid of fetuses and newborn infants with microcephaly showed that the virus shares 97% to 100% of its genomic identity with lineages isolated in the outbreak in French Polynesia in 2013. Research studies are being conducted, but at the time of this writing, no specific treatment or vaccines are available. People traveling to areas with autochthonus circulation of Zika virus should take measures to protect themselves from mosquito bites, and pregnant women should avoid traveling to endemic areas.